Doctors’ Knowledge, Attitude and Objective Adherence with Hypertension Guidelines in Quetta, Pakistan: A Cross-sectional Analytical Study - Khan, Mirza; Ahmed, Nafees; Wahid, Abdul; Ali Khan, Syed Liaquat; Khan, Asad; Akbar, Zarka; Bibi, Palwasha (Journal of Pharmacy Practice and Community Medicine)
Background: There is scarcity of published information about doctors’ knowledge, attitude and adherence with hypertension guidelines from Pakistan. Objectives: To evaluate doctors’ knowledge, attitude and objective adherence with the recommendations of Clinical Practice Guidelines (CPG) developed by American Society of Hypertension/International Society of Hypertension. Methods: This cross-sectional questionnaire-based study included 95 doctors from various health care facilities in Quetta, Baluchistan to evaluate doctors’ knowledge of and attitude towards guidelines. Physicians’ endearment with ASH/ISH (2014) guidelines was evaluated by the prescriptions they wrote to 1900 hypertensive individuals (20 prescriptions of each enrolled doctor). Data was analysed using SPSS 20. Results: 58.9% doctors had sufficient knowledge of guidelines. Doctors’ with specialization and consultants, doctors of age >35 years and who were in clinical practice for >5 years had significantly (p-value<0.05) greater knowledge and more guidelines adherent practices than their counterparts. There was a significant association between doctors’ knowledge and practice scores. (rs=0.758, p-value <0.001). Overall, doctors had positive attitudes towards guidelines. A total of 1385 (72.9%) prescriptions were judged guidelines adherent. In multivariate analysis, guidelines adherence had statistically significant positive association with the presence of any comorbidity (OR=2.804, p-value<0.001), heart failure (OR=5.101, p-value<0.001), chronic kidney disease (OR=2.384, p-value<0.001) and benign prostatic hyperplasia (OR=3.137, p-value=0.009) and negative association with diabetes mellitus (OR=0.265, p-value<0.001). Conclusion: Only 58.9% doctors were adequately aware of guidelines recommendations. A fair number of patients (72.9%) received guidelines adherent prescriptions. Doctors’ poor knowledge of guidelines preferred antihypertensive agents in diabetic hypertensive patients reflected in their practices.
Keywords: Diabetes mellitus; Duration of clinical practice; Guidelines adherence; Hypertension; Pakistan